Binary ionic iron(III) porphyrin nanostructured materials with catalase-like activity. (December 2020) - Rebelo, Susana L.H.; Neves, Cláudia M.B.; de Almeida, Miguel P.; Pereira, Eulália; Simões, Mário M.Q.; Neves, M. Graça P.M.S.; de Castro, Baltazar; Medforth, Craig J.
Highlights: Binary Fe(III) porphyrin structures were prepared by ionic self-assembly in water. The nanostructured materials were explored as enzyme models. Catalase-like activity significantly improved for ionic solids compared to metaloporphyrins. The effects of structure and electronic properties of the metaloporphyrin building blocks were evaluated. Materials were characterized before and after catalysis by SEM, XPS, DLS/ELS and UV-vis. Abstract: Supramolecular structures were prepared in water by ionic self-assembly of oppositely charged iron(III) porphyrins and tested as a new class of catalase mimics. Iron(III) porphyrins carrying the positively charged groups, N -methyl-4-pyridinium (FeTMPyP), 4-pyridinium (FeTHPyP) and tetrafluoro-4-imidazoliumphenyl (FeTFHImP) were assembled with iron tetrakis(4-sulfonatophenyl)porphyrin (FeTSPP), at an optimized pH. The material with the best catalase activity (FeTHPyP:FeTSPP) showed 65-77 catalase units (U)/mg in the pH range 3.5-7.0, which was significantly higher than the 3 U/mg observed for the individual porphyrins. Analogous metal-free structures had no catalytic activity. Micro-scale structures with nanoscale features were observed by Scanning Electron Microscopy. Studies of the chemical composition of materials by X-ray Photoelectron Spectroscopy showed the formation of structures with a 1:1 ratio for (+):(‒) tectons. Characterization of particles in solution was carried out at different pH and before and after catalysis by UV-vis spectroscopy, Dynamic Light Scattering (measurement of hydrodynamic diameters) and Electrophoretic Light Scattering (measurement of zeta potentials). Graphical Abstract: Image, graphical abstract